PENGARUH PAJAK PENGHASILAN BADAN TERHADAP LABA PERUSAHAAN PADA PT. FASTRATA BUANA - Wahyu Widodo; Mamay Komarudin; Munawaroh Munawaroh (Nindikayla Institute, 2023)
This study aims to determine whether there is any effect of the Corporate Income Tax Income In. Fastrata Buana. The research method used by the author is descriptive analytical method. Descriptive method aims to determine the nature and deeper relationship between the two variables by observing certain aspects. The data analysis technique used is the linear correlation analysis that aims to determine whether there is a relationship between the two variables, and simple linear analysis to determine the influence of the two variables, namely the corporate income tax (X) and Income (Y). To make it easier to analyze the data, the authors using SPSS v. 20. Based on the conclusion, that there is a very strong influence of the Corporate Income Tax (X) with Income (Y). the correlation value of 0,995. Then the contribution of corporate income tax variable (X) in the calculation of the variable explaining Income (Y) was 99% the remaining 1% balance of influenced by other factors. And linear regression equation  sobtainedareasfollows: Y = -46.66.087.488 + 3,841 X. In a hypothesis test, t test was concluded on Ho is rejected and Ha accepted. Means the Income Tax variables (X) has a significant effect on the Company Earnings variable (Y). It shows the value of t is greater than t table (17,647 > 3,182), so that Ho is rejected and Ha accepted. This means that